Avaliação da capacidade coagulante e atividade proteolítica de extrato gástrico de coelhos adultos para elaboração de queijo de massa semi-cozida tipo prato - Jiménez, Maximiliano Segundo Escalona (2023)
The search for substitutes for renin or chymosin for cheese making has stimulated the study of alternative sources including non-conventional animal species in order to develop enzymatic coagulants with technological properties similar to commercial coagulants. In the present study, the results of the evaluation of the coagulant capacity of the gastric extract of adult rabbits (GER) and its influence on the characteristics of Prato Type cheese are presented. Initially, rabbit stomachs aged 16 to 20 weeks were analyzed, determining extraction conditions such as direct salting or submersion in saline solution, in addition to testing different pH and incubation times for the conversion of pro-enzymes into active enzymes. The degree of hydrolysis of the extract over casein was evaluated through polyacrylamide gel electrophoresis and compared with commercial coagulant chymosin produced by fermentation (QC). For the coagulation tests, a Prato Type cheese was developed, and the physical-chemical, texture and proteolysis characteristics of the cheeses were verified during 60 days of storage. Salting in saline solution was more efficient for extracting the enzymes and pH 4.3 with an incubation time of 24 hours allowed reaching the maximum coagulation capacity of the GER. Compared with the QC, the cheeses showed similar characteristics in terms of proximate composition, with minimal variations in salt content, which was higher in the cheese made with GER. Knowing the optimal conditions for extracting the enzymes, a coagulant was prepared and the presence of enzymes was confirmed through electrophoresis, comparing the molecular weight with known standards and commercial coagulants such as renin obtained from bovine abomasum (RB) and QC, being verified the influence of GERD on the lipid profile of Prato cheese. It was verified that the composition was similar between treatments and, likewise, the fatty acid profile for cheese with 30 days of storage was similar between treatments, whose differences were observed mainly due to the evaluation period and not due to the influence of the coagulant. Rabbit are an alternative in the preparation of coagulants for cheese making, thus taking advantage of this residue from the slaughter of rabbits with little commercial value.